Learning of Greater Bangkok Health Service Systems from Quantitative Data during COVID-19 Pandemics of Delta Variant - พรรณารุโณทัย ศุภสิทธิ์; พรรณารุโณทัย กานต์; พรรณารุโณทัย พฤทธิกร; ศรเกษตริน อติญาณ์; วงศ์วิวัฒน์ ณัฐพงศ์; ชื่นกลิ่น ธัญพร; ศรียะศักดิ์ อัจฉราวดี; แก้ววิเชียร นภัส; แสงทอง วรวุฒิ; นิ้มวัฒนากุล สุชาดา; สุธรรมชัย เบญจพร (Journal of Health Science of Thailand, 2025)
The size of COVID-19 Delta variant pandemics started to challenge health service systems in Greater Bangkok before the rest of Thailand. The aim of this study was to analyze the dynamics of infections and health service systems responses from health management information systems designed during the pandemics. The secondary data from 2 databases (Co-Lab and Co-ward) during March to December 2021 were analyzed. The descriptive statistics on frequency and percentage were presented. Data on infected persons from both databases showed discrepancies as they were developed for different purposes. Outbreak rate estimated from Co-Ward database was as highest for Samut Sakhon, more than double the rate for Bangkok. The number of hospital beds reported in the Co-Ward database were 154,942 beds, of which 14% were reported from Bangkok, and increased to 23% if covered Greater Bangkok (Bangkok and 5 perimeter provinces). The bed crisis was first found in Bangkok, in the 18th week of 2021, with reported patients treated in the cohort intensive care unit (ICU) beds since week 17. The crisis kept continue to the peak of week 34 at 400 occupancy beds per week (or 57 beds per day) in Bangkok that started rising in week 18. Then in week 19 the cohort ICU were appeared. Intensive beds were peak in week 34 with more than 400 beds/week (57 beds/day). Bed crisis in Samut Sakhon occurred immediately after Bangkok and lasted longer. Samut Sakhon had higher proportion of beds from private sector, with high outbreak rate so high burdens on bed uses. The lessons learned from Greater Bangkok were summarized. At the critical situations, new patterns of health services were created. The management information systems needed to be live-implemented and adjusted till the benefit of daily management achieved. Dangerous infectious disease laws and medical practice guidelines needed to be timely updated to be appropriately with the dynamic nature of the disease. Holistic approaches integrating entire health systems efforts helped prevent Greater Bangkok from failed hospital system.